2014
DOI: 10.1371/journal.pone.0102370
|View full text |Cite
|
Sign up to set email alerts
|

Absence of BRCA/FMR1 Correlations in Women with Ovarian Cancers

Abstract: Previously reported findings in Austrian BRCA1/2 mutation carriers suggested a possible dependency of embryos with BRCA1/2 mutations on so-called low alleles of the fragile X mental retardation 1 (FMR1) gene, characterized by less than 26 CGG repeats (CGGn<26). The hypothesis arose from a study reporting highly statistically significant enrichment of low FMR1 alleles, significantly exceeding low allele prevalence in a general population, suggesting embryo lethality of BRCA1/2 mutations, “rescued” by presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The DOCK4 functions as a guanine nucleotide exchange factor and is involved in regulation of adherens junctions between cells and in cell migration, could suppresses tumor invasion in osteosarcoma mouse cell lines [ 34 36 ]. FMR1 may be involved in the regulation of ATR-dependent signaling pathways such as BRCA1 phosphorylations and interact with BRCA in human Ovarian Cancers [ 37 ]. ZFHX3 may function as transcriptional regulator and was reported to participate in gastric cancer by regulating MUC5AC promoter [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DOCK4 functions as a guanine nucleotide exchange factor and is involved in regulation of adherens junctions between cells and in cell migration, could suppresses tumor invasion in osteosarcoma mouse cell lines [ 34 36 ]. FMR1 may be involved in the regulation of ATR-dependent signaling pathways such as BRCA1 phosphorylations and interact with BRCA in human Ovarian Cancers [ 37 ]. ZFHX3 may function as transcriptional regulator and was reported to participate in gastric cancer by regulating MUC5AC promoter [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Through differential gene-expression analysis and Venn diagram analysis of mRNAs and host genes of circRNAs, we found eight genes in common: in which four gene are tumor-related, including Dock4 , Fmr1 , Zfhx3 , Ralb . These genes have been reported in cancers or tumors in human [ 34 , 37 39 ].We characterized circRNA catalogs in chickens, compared them with mRNAs and lncRNAs and found that in chickens, circRNAs have relatively shorter transcripts and similar GC content, these characteristics are similar to lncRNAs in chicken in our previous study [ 46 ]. We also found that one gene could produce multiple circRNAs in chicken, which is consistent with results in human [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Yet, unlike the almost complete absence of long CGG repeat sizes (34 repeats and above) in the study by Weghofer and co-workers (2012), in the present study 8·5% of BRCA1/BRCA2 carriers had at least one long CGG allele, a rate that was not statistically different to that of the control population (12·9%). Another recent study that focused on ovarian cancer cases (n = 87) showed that ovarian cancer cases who are BRCA pathogenic mutation carriers (n = 15) exhibit a normal-range prevalence of FMR1 CGG alleles, whereas ovarian cancer patients who are BRCA wildtype, display a trend (not reaching statistical significance) towards higher prevalence of low CGG repeats of the FMR1 gene (Gleicher et al, 2014). In line with our previous data, smaller studies published from Israel (Dagan et al, 2014), Italy (Ricci et al, 2014) and Holland (Brandão et al, 2013) also failed to show the lack of long CGG FMR1 alleles in BRCA mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis behind this finding is that BRCA1/2 mutations are embryo-lethal but can be rescued by low CGG repeats in the FMR1 gene, and thus women with low CGG repeat length should have an increased risk for BRCA-associated cancers. However, several similar studies have since been conducted and have found no differences in the distribution of FMR1 repeat length between BRCA1/2 mutation carrier women and controls (Dagan et al 2013;Gleicher et al 2014a;Ricci et al 2014). Therefore, a newer hypothesis exists that only certain BRCA1/2 mutations are embryo lethal, requiring rescue by a low FMR1 allele to survive (Gleicher et al 2014b).…”
Section: Introductionmentioning
confidence: 99%